Reelin promotes cerebral angiogenesis via mTOR/HIF-1α-mediated transcriptional upregulation of Netrin-4 - Zhaowei Feng; Meihua Pan; Hui Liu; Meiting Liu; Jiahui Yang; Chun-yu Wang; Ruiqin Yao; Haiyan Liu; Yanyan Fu (Tissue and Cell, 2026)

Interpretable machine learning for optimization of ultrasound-assisted polysaccharide extraction using natural deep eutectic solvents: From yield enhancement to structural and antioxidant activity validation - Shulu Zhang; Jingting Han; Ruichen Gao; Yeqing Xu; Zheng Feng; Xinhui Huang; Yinze Zhong; Qingxia Wang; Xinran Yu; Siyu Chang; Meiting Jiang; Zhibin Wang; et al. (Bioresource Technology, 2026)

Integrated deep learning and multi-scale modeling for the discovery of pan-genotypic HCV NS5B polymerase inhibitors - Di Han; Fengxiang Liu; Xiangbing Peng; Yifan Wang; Zhipeng Shi; Yiwei Xue; Hongkun Yang; Meiting Wang; Jiarui Lu; Taigang Liu; Shaoli Cui; Yongtao Xu (Molecular Diversity, 2026)

Molecular epidemiology and genetic diversity of carp edema virus (CEV) in China (2013–2019): New insights into transmission and diagnosis - Tinhan Chien; Chuwei Ma; Junqi Wang; Weizhong Tian; Shifu Kan; Xuebing Yang; Shaolin Tang; Meiting Lee; David Stone; Sophie St-Hilaire; Hsien-Da Huang; Hong Liu; et al. (Aquaculture, 2026)

Built-in electric field constructed by asymmetric electron cloud distribution for facilitating photocatalytic H2O2 production in covalent organic frameworks - Chuanxue You; Yue Zhou; Meiting Yang; Jingyang Li; Bo Hu; Yunchao Ma; Linlin Liu; Chunbo Liu; Guangbo Che (Journal of Environmental Chemical Engineering, 2026)

Decoding the interaction of characteristic aroma compounds in Anhui rose damascena essential oil: Utilizing odor activity values, molecular simulation, and machine learning - Xinyi Yang; Mengdong Qiao; Wenbo Bai; Meiting Zhao; Siqi Sun; Zengyang He; Zhiqiang Xu; Yunwei Niu (Food Chemistry, 2026)

Safety Evaluation of Human-Derived Uric Acid Degrading Lacticaseibacillus paracasei M2a and Its Impact on Gut Microbiota - Wujin Chen; Tingting Tian; Jingru Zhou; Dan Yang; Meiting Liang; Yi He; Shanshan Yang; Dilinuer Aikepa; Yuping Sun (Probiotics and Antimicrobial Proteins, 2026)

Modulation of the gut-skin axis by polysaccharides: Mechanisms and therapeutic potential in immune-related skin diseases - Chen Haiming; Liao Yijing; Tang Bin; Ma Xiaoyu; Li Hailun; Dong Meiting; Li Ziqing; Zheng Xuwei; Yang Yujie; Su Zuqing; Li Shaoping; Lu Chuanjian (Carbohydrate Polymers, 2025)

Toward carbon peak in China's manufacturing sector: Robot adoption and capital‐embodied technological progress - Xi Zhang; Xiaoqian Song; Meiting Fan; Beijia Huang; Hongmei Yang; Shuai Shao; Yong Geng (Journal of Industrial Ecology, 2025)
China's manufacturing sector has experienced increasing robot adoption and capital‐embodied technological progress, accompanied by massive energy consumption and carbon emissions. The robot adoption brings technological and environmental risks in the manufacturing sector. Based on the data of 28 manufacturing sub‐sectors, this study uses the logarithmic mean Divisia index method to investigate the contributions of robot adoption, labor, capital, and energy factors to the changes in carbon emissions in China's manufacturing sector. Furthermore, we conduct the scenario analysis and Monte Carlo simulation to project the future trajectories of carbon emissions in China's manufacturing sector under the different scenarios until 2035. Results show that during 2006–2019, both scale effect and technical effect driven by robots contributed to carbon emission reduction. Robot scale was the dominant contributor to the carbon emission increase, followed by capital automation. On the contrary, the workforce structure and energy‐robot structure played dominant roles in carbon emission reduction. Labor productivity, capital deepening, and the carbon intensity of energy exerted marginal effects on carbon emissions. During 2020–2035, carbon emissions will increase consistently from 62.4 million tons (Mt) to 72.6 and 228.2 Mt under the business‐as‐usual scenario and higher‐emission scenario, respectively, while they will have obvious inflection points under other three scenarios. Carbon emissions will peak at 65.3 Mt in 2023 and have the largest mitigation potential in the lower‐emission scenario. Finally, several policy suggestions are raised for China to build a manufacturing system with the coordinated development of intelligence and low carbon.

Clay minerals limit nanoplastic uptake in wheat plant - Jie Yang; Chen Tu; Ruijie Li; Lianzhen Li; Ying Liu; Zijian Liu; Meiting Chi; Yongming Luo (Journal of Hazardous Materials, 2025)

N–doped carbon coating boosts the construction of high–performance regenerated LFP cathodes - Yifeng Li; Haoxuan Yu; Yuan Ding; Meiting Huang; Yaohui Xie; Peilin Li; Zhihao Wang; Lihua Wang; Liang Chen; Xubiao Luo; Liming Yang (Chemical Engineering Journal, 2025)

A novel method to repair and upgrade spent LFP cathode material by inherent Al impurity doping - Haoxuan Yu; Derun Zhao; Kechun Chen; Meiting Huang; Haitao Yang; Liming Yang; Zhihao Wang; Liang Chen; Xuan Ding; Hui Lv; Xubiao Luo (Resources, Conservation and Recycling, 2025)

Fluoride ion-mediated differential coordination separation of Al (III) and Fe (III) for regeneration of low-aluminum, high-purity battery-grade iron phosphate - Fei Han; Yaohui Xie; Lin Qu; Zhenzhou Wang; Wei Zhang; Guang Yang; Huiqin Hu; Meiting Huang; Haoxuan Yu; Liming Yang; Xubiao Luo (Resources, Conservation and Recycling, 2025)

Inherent fluorine impurity enhances the regeneration of highly degraded layered cathodes with suppressed lattice oxygen escape - Meiting Huang; Haoxuan Yu; Liang Chen; Haitao Yang; Zhihao Wang; Yifeng Li; Kechun Chen; Chenxi Xu; Liming Yang; Xubiao Luo (Chemical Engineering Journal, 2025)

OncomiR mdv1-miR-M7-5p promotes avian lymphomatosis by modulating the BCL2/Bax mitochondrial apoptosis signaling pathway - Jun Zhou; Fan Yang; Congsen Zheng; Yanting Chen; Meiting Chen; Qiaoer Lin; Chuanzhe Chang; Shikai Cai; Zhaoyang Sun; Hua Li; Limei Qin; Yanfeng Chen (Veterinary Microbiology, 2025)

SaTDT enhanced plant tolerance to NaCl stress by modulating the levels of malic acid and citric acid in cells - Xiangyu Wei; Li Xu; Suisui Dong; Nina He; Qianqian Xi; Dan Yao; Qianqian Wang; Yue Zuo; Chen Ling; Meiting Qi; Wen Bai; Kai Han; et al. (Plant Molecular Biology, 2025)

Machine learning prediction for constructing a universal multidimensional information library of Panax saponins (ginsenosides) - Hongda Wang; Lin Zhang; Xiaohang Li; Mengxiao Sun; Meiting Jiang; Xiaojian Shi; Xiaoyan Xu; Mengxiang Ding; Boxue Chen; Heshui Yu; Zheng Li; Dean Guo; et al. (Food Chemistry, 2024)

Alkali-enhanced polyvinylidene fluoride cracking to deeply remove aluminum impurities for regeneration of battery-grade lithium iron phosphate - Fei Han; Lei Zhou; Difan Fang; Guang Yang; Liming Yang; Meiting Huang; Yufa Feng; Penghui Shao; Hui Shi; Xubiao Luo (Chemical Engineering Journal, 2024)

Degradation of levofloxacin from antibiotic wastewater by pulse electrochemical oxidation with BDD electrode - Tao Xu; Xiting Tang; Meiting Qiu; Xiaoliu Lv; Yang Shi; Yihui Zhou; Yanfei Xie; Mu. Naushad; Su Shiung Lam; Hui Suan Ng; Christian Sonne; Shengbo Ge (Journal of Environmental Management, 2023)

Fabrication and optimization of paper chips from calcinated Fe-MOFs for rapid and in situ visual detection of tetracyclines in water environments - Cuizhu Sun; Chenguang Li; Meiting Guo; Xianghao Yang; Yadan Luo; Lingyun Chen; Hao Zheng; Shasha Zhao; Fengmin Li (Journal of Hazardous Materials, 2023)

Soy protein isolate-polyguluronate nanoparticles loaded with resveratrol for effective treatment of colitis - Wenhao Li; Decheng Bi; Jiang Yi; Lijun Yao; Jue Cao; Peng Yang; Meiting Li; Yan Wu; Hong Xu; Zhangli Hu; Xu Xu (Food Chemistry, 2023)

Histone modification landscape and the key significance of H3K27me3 in myocardial ischaemia/reperfusion injury - Le Ni; Bowen Lin; Yanping Zhang; Lingjie Hu; Jianghua Lin; Fengmei Fu; Meiting Shen; Can Li; Lei Chen; Jian Yang; Dan Shi; Yi-Han Chen (Science China Life Sciences, 2023)

Carbon regulation and economic growth: City-level evidence from China - Zhenbing Yang; Minwei Lu; Shuai Shao; Meiting Fan; Lili Yang (Environmental Impact Assessment Review, 2023)

Regional water pollution management pathways and effects under strengthened policy constraints: the case of Tianjin, China - Yujia Wang; Mo Zhang; Chonggang Yang; Yan He; Meiting Ju (Environmental Science and Pollution Research, 2022)

Effect of operating parameters on hydrothermal liquefaction of corn straw and its life cycle assessment - Shiqiu Zhang; Shengnan Zhou; Xue Yang; Wen Xi; Kui Zheng; Chunli Chu; Meiting Ju; Le Liu (Environmental Science and Pollution Research, 2020)

Mercury adsorption to aged biochar and its management in China - Shiqiu Zhang; Xue Yang; Meiting Ju; Le Liu; Kui Zheng (Environmental Science and Pollution Research, 2019)

Analysis of soil risk characteristics by comprehensive assessment in an industrial area of China - Yang Guan; Chaofeng Shao; Lei Kang; Xin Li; Meiting Ju (Environmental Science and Pollution Research, 2018)

Study of a comprehensive assessment method of the environmental quality of soil in industrial and mining gathering areas - Yang Guan; Chaofeng Shao; Qingbao Gu; Meiting Ju; Xueju Huang (Stochastic Environmental Research and Risk Assessment, 2016)